Surviving stalking - Pathé, Michele, 1959- (Cambridge books online., 2002)
This is the first accessible, contemporary account of victim types, stalker types, stalkers' motives, strategies to prevent and overcome stalking, legal guidance, and further resources. It will be of interest not only to victims of stalking, but also to the health and legal professionals who work with them.